1995
DOI: 10.1172/jci117842
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of reactive oxygen intermediates in cyclooxygenase-2 expression induced by interleukin-1, tumor necrosis factor-alpha, and lipopolysaccharide.

Abstract: Reactive oxygen intermediates (ROIs) play an important role in inflammatory processes as mediators of injury and potentially in signal transduction leading to gene expression. Cyclooxygenase (COX) is a rate-limiting enzyme in prostanoid biosynthesis, and its recently cloned inducible form, COX-2, is induced by proinflammatory cytokines. This study linked ROIs to the signaling pathways that induce COX-2 expression. The hydroxyl radical scavengers DMSO (1% ), as well as di-and tetramethylthiourea, inhibited IL-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
259
2
6

Year Published

1996
1996
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 453 publications
(281 citation statements)
references
References 39 publications
(24 reference statements)
14
259
2
6
Order By: Relevance
“…The WD increased COX2 and angptl2 expression, two markers of inflammation, in CAT mice only. We previously reported that COX2 expression correlated with the level of damage in endothelial cells isolated from coronary artery disease patients [75], while others showed that oxidative stress stimulated COX2 expression [21]. In addition, we reported that 9 months of CAT magnified 50-folds the rise in COX2 expression associated with aging in the mouse aorta [26].…”
Section: Inflammationmentioning
confidence: 77%
“…The WD increased COX2 and angptl2 expression, two markers of inflammation, in CAT mice only. We previously reported that COX2 expression correlated with the level of damage in endothelial cells isolated from coronary artery disease patients [75], while others showed that oxidative stress stimulated COX2 expression [21]. In addition, we reported that 9 months of CAT magnified 50-folds the rise in COX2 expression associated with aging in the mouse aorta [26].…”
Section: Inflammationmentioning
confidence: 77%
“…5-Hydroxytryptamine (5-HT), through its receptor 5-HT2A, induced MAPK/MEK via ROS production, which in turn leads to stimulation of TGF-␤ (90). Interleukin-1 (IL-1), TNF-␣, and lipopolysaccharide (LPS) induced COX-2 expression, a generator of proinflammatory prostanoids, and blockade of NAD(P)H oxidase abrogated TNF-␣-mediated effects (67). Homocysteine was shown to stimulate NAD(P)H-dependent ROS production through Rac1, and this was mediated by vav2, a guanine nucleotide exchange factor (GEF).…”
Section: B Ros and The Glomerular Basement Membrane (Gbm)mentioning
confidence: 99%
“…Reactive oxygen species themselves can increase and/or induce cellular cyclooxygenase-2 (COX-2) expression [8][9][10] . In addition, apoptotic cell death induced by exposure to cyanide can be inhibited by selective COX-2 inhibition [11,12] .…”
Section: Introductionmentioning
confidence: 99%